Tubular Adenoma of the Breast: A Clinicopathologic Study of a Series of 9 Cases - Boubacar Efared; Ibrahim S Sidibé; Souley Abdoulaziz; Nawal Hammas; Laila Chbani; Hinde El Fatemi (SAGE Publishing, 2018)
Tubular adenoma of the breast is one of the most rare benign neoplasms, accounting for only 0.13% to 1.7% of all breast benign tumors. Little is known about this rare neoplasm as the current literature offers only some case reports or a few number of small series. The aim of our study is to provide some clinicopathologic features of the breast tubular adenoma. We retrospectively analyzed at our department of pathology all cases of breast tubular adenomas confirmed by immunohistochemistry over a period of 9 years (2009-2017). Nine cases of breast tubular adenoma have been recorded, with an average age of 31.44 years. Five tumors were located at the right side (55.55%), and most cases had suspicious aspects on imaging techniques (6 cases out of 9). The diagnosis has been made on 5 resected specimens (lumpectomy) and on 4 core needle biopsies. The tumor size ranged from 0.9 to 7 cm (mean size of 3.08 cm) and had well-circumscribed margins with elastic consistency. The histopathologic analysis showed a typical pattern of proliferating round and uniform tubules lined by regular epithelial cells surrounded by myoepithelial cells, packed in a small amount of stroma, highlighted by CD34 immunostaining. Tubular adenoma is a rare breast benign neoplasm of young premenopausal women. The radiologic aspects are often worrisome and only the histopathologic analysis can achieve the correct definitive diagnosis by excluding all potential differential diagnoses.